Indonesia DIA-RAMADAN Study: A Real-life, Prospective and Observational of Gliclazide MR in Type-2 Diabetes Patients During Ramadan Fasting - Soebagijo Adi Soelistijo; Andi Makbul Aman; Hendra Zufry; Agung Pranoto; Achmad Rudijanto; Mohamed Hassanien (Acta Medica Indonesiana, 2022)
Background: Sulfonylureas (SUs) have been widely used in many countries for T2DM treatment. Gliclazide is one of the SUs with the lowest risk of hypoglycemia; however, the safety and effectiveness of gliclazide MR during Ramadan has not yet been reported in Indonesia. This study aimed to assess safety, efficacy, and tolerability of gliclazide modified release (MR) during Ramadan fasting. Methods: The study was a part of DIA-RAMADAN study, a prospective observational study with subjects of T2DM patients aged >18 years, who had either controlled or sub-optimally controlled blood glucose level, performed Ramadan fasting. Subjects had been treated with gliclazide MR for at least 90 days prior the study, and were examined for their body mass index (BMI), fasting plasma glucose (FPG) and HbA1c levels 6 to 8 weeks before Ramadan (V0) and 4 to 6 weeks after the end of Ramadan (V1). Results: Out of 198 subjects participating in the study, there were only two subjects (1.0%) who reported symptomatic HEs (either confirmed or not confirmed) and no severe HEs had been reported. There were no significant changes in HbA1c and FPG levels (p>0.05). Interestingly, there was a reduction of bodyweight (-0.4kg) from pre- to post-Ramadan (p < 0.001). Almost no subjects reported discontinuation of gliclazide MR throughout the entire study; however, there was one subject who reported a change of diabetic treatment into diet only. Conclusion: gliclazide MR is safe, well tolerated and can maintain glycemic control effectively for Indonesian patients with T2DM who perform Ramadan fasting.